Spirit Konfusianisme Korea Selatan dalam Dominasi Ekonomi di Asia Timur: Studi Tentang Samsung Group - Fatah, Atief Arezal; Kurniawati, Kurniawati (Universitas Sebelas Maret, 2025)
This research aims to reveal the factors of South Korea's success in strengthening economic dominance in the East Asia or regional region, through the landscape of the Samsung Group Multinational Company and the importance of Confucianism that forms the historical & cultural background of South Korean society. The method used is Descriptive Narrative in a historical approach. The findings indicate a strong relationship between South Korea’s economic resurgence, the strategic role of large conglomerates (chaebol) such as the Samsung Group, and the internalization of Confucian values as a cultural belief system embedded in various aspects of social and economic life. The study concludes that Confucian teachings, particularly those related to discipline, hierarchy, loyalty, and work ethic have significantly contributed to societal participation and corporate growth in South Korea, as reflected in the rapid development and global expansion of major corporations, including the Samsung Group.